Sensus sampel perikanan laut, sensus sampel perikanan tambak (Biro Pusat Statistik, Kantor Statistik Propinsi Jawa Barat, 1985)
Statistics on marine fish and fish pond products in Jawa Barat Province; results of the 1983 Agricultural census.